Evaluasi Pelaksanaan Asesment Autentik Dalam Pembelajaran Ekonomi di Sekolah Menengah Ata - Noviatri indah Puspita sari; Rosmiati Rosmiati; Frin Eben; Sindi Mertisia (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2023)
This study aims to determine the implementation of authentic assessments in economics learning in accordance with the 2013 curriculum at Muaro Jambi 6th State Senior High School and also to see whether there are any obstacles to economics teachers when implementing the 2013 curriculum in implementing authentic assessments. The research method used in this research is descriptive qualitative method using the stake evaluation model. Data collection techniques are in the form of observation, questionnaires, and literature studies on syllabus and lesson plans .The results of this study are (1) Authentic assessment procedures in economic learning are going well. At the planning stage, a percentage of 85.33% was obtained in the good category. At the implementation stage, a percentage of 77.7% was obtained in the sufficient category. At the yield stage, a percentage of 81.25% is obtained; (2) The teacher's constraints in implementing authentic assessment in economics learning are limited time constraints in one lesson, the many indicators of authentic assessment, and also the lack of student motivation in participating in innovative learning with authentic assessment and infrastructure that does not function properly